2021
DOI: 10.1016/j.ajpath.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Phase Imaging Reveals Spatial Heterogeneity of Extracellular Vesicles in Select Colon Disorders

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…The decrease in cell volume of CCD-18Co and LoVo cells in a hypoxic milieu was associated with the opposite tendency that occurred in HT-29 cells. Quantitative analysis of the variation of the average RI of whole cells ( Figure 4 E) indicated that adenocarcinoma cells (HT-29, LoVo) had significantly higher RI values than normal epithelial cells, particularly HT-29 cells, correlating with our previous results [ 35 ]. However, hypoxia induced a statistically significant decrease in the RI values of the observed cells, suggesting that local changes occur in the density and chemical composition of the cellular content.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The decrease in cell volume of CCD-18Co and LoVo cells in a hypoxic milieu was associated with the opposite tendency that occurred in HT-29 cells. Quantitative analysis of the variation of the average RI of whole cells ( Figure 4 E) indicated that adenocarcinoma cells (HT-29, LoVo) had significantly higher RI values than normal epithelial cells, particularly HT-29 cells, correlating with our previous results [ 35 ]. However, hypoxia induced a statistically significant decrease in the RI values of the observed cells, suggesting that local changes occur in the density and chemical composition of the cellular content.…”
Section: Resultssupporting
confidence: 89%
“…Since it was not possible to directly indicate that the observable spheroid-shaped structures were vesicles or lipid droplets, in this model, it was assumed that the refractive index increment is equal to 0.160 mL/g and that they contain proteins and lipids. Next, to analyze changes in the size distribution of these structures inside the cell under hypoxia stress, RI data processing from our previous work was applied [ 35 ]. The series of 2D-RI tomograms were digitally stained based on the determined RI values to indicate the spatial location of vesicles/lipid droplets, and after contrast enhancement, they were converted to binary masks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we described a plasmonic system based on a nanohole array biosensor to discriminate live single cancer cells from normal cells [ 23 ]. Other techniques, including confocal refractive index microscopy, terahertz spectroscopy and quantitative phase imaging [ 24 , 25 , 26 ], have been used for label-free imaging of living cells or cell-derived structures. The confocal imaging techniques have an advantage in investigating whole cells, which is due to their larger propagation depth, when there are no specific subcellular structures to target.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to diagnose cancer based on a transparent relationship with cancer, such as the case where melanoma-derived exosomes were detected in bodily fluid samples based on the CSPG4 protein expressed in melanoma, phenotypic issues need to be specified prior to experimentation. Recently, studies have been conducted to characterize the phenotype of exosomes using IR spectroscopy [ 58 , 59 ], optical methods [ 60 , 61 , 62 ], and cryo-transmission electron microscopy-based analysis methods [ 57 ].…”
Section: Introductionmentioning
confidence: 99%